Pengaruh Etos Kerja Islam Terhadap Kepuasan Kerja Karyawan Pada Waroeng Steak and Shake Surabaya - Harjanto Saputro; Ari Prasetyo (Universitas Airlangga, 2014)
This research was aimed to investigate the effect of Islamic work ethics to the employee Satisfaction on Waroeng Steak & Shake in Surabaya. This study used questionnaires in primary data collection and quantitative approaches. Experiments were done using simple linear regression, where the dependent variable (Y) is the employee work satisfaction and the independent variable (X) is Islamic work ethics. The research sample were taken by census. The research sample was 33 employees working in Waroeng Steak & Shake Surabaya.Based on the findings, it obtained simple linear regression equation : Y = 0,929 + 0,684X. The magnitude of the influence of Islamic work ethics to the employees work satisfaction on Waroeng Steak & Shake in Surabaya is the R2 value of 0,423 (42,3%). The result show that employee work satisfaction on Waroeng Steak & Shake in Surabaya significantly affect by Islamic work ethics. REFERENCESAhmad, Mustaq. 2001. Etika Bisnis Dalam Islam. Jakarta: Pustaka Al-Kautsar.Ali, J.A. and Al-Owaihan, A. 2008. ”Islamic work ethic: a critical review” Cross Cultural Management an International Journal. Vol. 15 No. 1As’ad, Mohamad. 2004. Psikologi Industri.Yogyakarta: Liberty. Asifudin, Ahmad. 2006. Etos Kerja Islami. Yogyakarta : UII Press.Azis Slamet Wiyono dan M. Wahyuddin, 2005, Studi Tentang Kualitas Pelayanan dan Kepuasan Konsumen di Rumah Sakit Islam Manisrenggo Klaten, Program Pascasarjana Universitas Muhammadiyah Surakarta Jalan A. Yani, Tromol Pos 1, Pabelan, Surakarta 57102.Azizi, Moh Ali. 2005. Dakwah Pemberdayaan Masyarakat Paradikma Aksi metodologi.Yogyakarta : Pustaka Pesantren Blum, M.L. 1956. Industrial Psichology and Its Socal Foundation. New York: Harper and Row Brown SP, Leigh TW. 1996. A New Look at Psyshological Climate and Its Relationship to Job Involvement, Effort and Performance. Journal of Applied Psychology. 81:358-368. Departemen Agama RI. 2012. Al-Qur’an dan Terjemahannya dengan Transliterasi. Semarang: PT Karya Toha Putra.Fakultas Ekonomi Universitas Airlangga. 2009. Pedoman Pelaksanaan Pendidikan Fakultas Ekonomi Universitas Airlangga. Surabaya: Fakultas Ekonomi.Hamzah, Ya’kub 1983. Etika Islam. Bandung: CV. DiponegoroHasibuan, Malayu. 2001. Manajemen Sumber Daya Manusia:Pengertian Dasar, Pengertian, dan Masalah. Jakarta: PT. Toko Gunung Agung.Hayati, Keumala. 2012. Islamic Work Ethic: The Role of Intrinsic Motivation, Job Satisfaction, Organizational Commitment and JobPerformance. Procedia - Social and Behavioral Sciences 65 ( 2012 ) 272 – 277Herman Soewardi. 2004. Sosiologi: Membangkitkan Karsa Umat. Tumpuan Utama Bagi Pembangunan. Bakti Mandiri. BandungJewell, L.N. dan Siegall Mac. 1988. Psikologi Industri Organisasi Modern. Edisi Kedua. Arcan. Lambert, E & Hogan, N 2009, “The importance of job satisfaction and organisational commitment in shaping turnover intent”, Criminal Justice Review, vol. 34, no. 1, pp. 96-118.Mangkunegara, Anwar Prabowo, 2005. Perencanaan dan Pengembangan Sumber Daya Manusia. Bandung: PT. Refika Aditama.Marri, Muhammad Yousuf Khan. 2012. The Impact of Islamic Work Ethics on Job Satisfaction and Organizational Commitment: A Study of Agriculture Sector of Pakistan. International Journal of Business and Behavioral Sciences Vol. 2, No.12; December 2012Robbins, S.P. 2006. Perilaku organisasi. Edisi Enam. Alih bahasa oleh Tim Indeks. Jakarta: PT.Indeks.Sinamo, Jansen. 2005. Delapan Etos Kerja Profesional; Navigator Anda Menuju Sukses. Bogor: Grafika Mardi Yuana.Sutrisno, Hadi. 2000. Metodologi Research. Jilid 2. Yogyakarta: Andi.Tasmara,Toto. 2002. Membudayakan Etos Kerja Islami. Jakarta : Gema Insan Press.Wexley, K.N. & Yukl, G.A. 1997. Organizational Behaviour and Personnel Psychology. Home Wood, Illinois: Richard D. Irwin, Inc.Yousef, Darwish A. 2000. Organizational Commitment As Amediator Of The Relaationship Between Islamic Work Ethic and Attitudes Toward Organizational Change. Journal Of Human Relation, Vol. 53, No. 4, September.